'The still-moving position' of the 'working-class' feminist academic: dealing with disloyalty, dislocation and discomfort. Issue 1 (2nd January 2021) - Wilson, Annabel; Reay, Diane; Morrin, Kirsty; Abrahams, Jessie
ABSTRACT: This paper examines the relationship of working-class feminist academics to the Academy. Our paper interrogates tensions between resistance and submission from the perspective of four educationally successful working-class women who have become academics. The paper starts with an overview of the state of the Academy at the beginning of the twenty-first century before addressing the conundrum that, for women from working-class backgrounds, success is often configured as, or feels like, failure. The paper develops and reflects on four central themes: the dilemmas of belonging within higher education, the challenge of continuing class exclusions, the oppressive and exploitative class relations that remain and are rarely recognised or addressed, and finally, the difficulties around sustaining 'authentic' and meaningful relationships with the still working-class. We conclude with questions and suggestions about what possibilities exist for those of us who grew up working-class to put into practice Bourdieu's injunction to be organic intellectuals.